2010
DOI: 10.1007/s00296-009-1345-1
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume in patients with rheumatoid arthritis: the effect of anti-TNF-alpha therapy

Abstract: A number of mediators are involved in the inflammatory processes that affect joints and vascular wall of patients with rheumatoid arthritis (RA). Tumour necrosis factor alpha (TNFa) is one such mediator, and it is widely regarded as an important target for anti-rheumatic treatment. Most recent studies show that anti-TNFa medication suppresses inflammation and reduces overall activity of RA. The aim of the current study was to investigate changes of mean platelet volume (MPV) in response to the 3-month anti-TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
150
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(160 citation statements)
references
References 31 publications
5
150
2
3
Order By: Relevance
“…Gasparyan et al [16] suggested two possible mechanisms of decreased MPV in high-grade inflammatory conditions. First is the overproduction of pro-inflammatory cytokines and acutephase reactants interfering with megakaryopoiesis which in turn results in subsequent release of small size platelets from the bone marrow.…”
mentioning
confidence: 99%
“…Gasparyan et al [16] suggested two possible mechanisms of decreased MPV in high-grade inflammatory conditions. First is the overproduction of pro-inflammatory cytokines and acutephase reactants interfering with megakaryopoiesis which in turn results in subsequent release of small size platelets from the bone marrow.…”
mentioning
confidence: 99%
“…MPV has been studied in various disease groups other than hematologic disease such as cardiovascular and rheumatic diseases [2][3][4][5]. It has been also investigated in several hepatic diseases and showed significant differences in these disease entities [1,[6][7][8][9][10].…”
mentioning
confidence: 99%
“…Thrombopoietin (TPO), which is synthesized in the liver, could play a relevant role to increase MPV in hepatic diseases. Moreover, in addition to TPO, several cytokines, inflammatory mediators, and growth factors may affect MPV, with subsequent production of larger and more reactive platelets [2][3][4][5]. These mechanisms could be involved in several hepatic diseases, such as CHB and HCC.…”
mentioning
confidence: 99%
“…In addition, recently, some studies have suggested that MPV can be used as marker of inflammation and disease activity [10,11]. Interestingly, it has been noted by Gasparyan et al [11] that the intensity of systemic inflammation determines the size of circulating platelet size.…”
Section: 1mentioning
confidence: 99%